2020
DOI: 10.34069/ai/2020.28.04.39
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for increasing exports of Russian wheat to the world market

Abstract: The article discusses the development of wheat export, which is the main grain crop in the structure of production and export of Russia. The record crop of grain crops in 2017 provided a good basis for the activation of Russian grain exporters in the world market. An analysis of geographical areas by source of grain export showed that crop growth allowed Russia to become a leader, as the main North American and European competitors experienced certain difficulties that led to a reduction in their export potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Countries in the Americas such as Oceania are not major importers, mostly meeting their own needs. In addition, Russian interest here is minimal, due to the geographical remoteness and the presence of large players in grain export -Canada, USA, Australia (Zyukin et al, 2020a). Proceeding from this, the Asian market, as the largest in terms of wheat imports and the fastest growing due to the countries of Southeast Asia, is the most attractive for Russia, for which a traditional pool of importers in the Middle East has already formed.…”
Section: Resultsmentioning
confidence: 99%
“…Countries in the Americas such as Oceania are not major importers, mostly meeting their own needs. In addition, Russian interest here is minimal, due to the geographical remoteness and the presence of large players in grain export -Canada, USA, Australia (Zyukin et al, 2020a). Proceeding from this, the Asian market, as the largest in terms of wheat imports and the fastest growing due to the countries of Southeast Asia, is the most attractive for Russia, for which a traditional pool of importers in the Middle East has already formed.…”
Section: Resultsmentioning
confidence: 99%
“…As some researchers note, in 2006, 11 million tons of wheat were exported abroad, in 2012 -22 million tons, in 2015-2016 -33.9 million tons, in 2016-2017 -35.5 million tons, in 2017-2018 -52.4 million tons, while in 1999, the amount of grain export was only 0.8 million tons [9]. The developing countries of Africa and Asia are the main sales market for Russian grain, while Egypt and Turkey are the main importers of Russian wheat [10]. There is no export of this type of product to the developed countries of the world, in particular to the European Union, since for the EAEU countries an individual sub-quota for grain imports, including wheat, is not provided [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Russian pricing practices could influence food supply in these developing nations that rely heavily on imports. Zyukin et al (2020) indicated that Russia has recently become one of the world's top wheat exporters, vigorously pushing its goods in the rapidly rising Asian and African markets. Central and South Africa is a relatively…”
Section: Food Exports From Russia and Ukraine To The African Continentmentioning
confidence: 99%